Developing Bilingual Website for Cussaybienna Micro Small Medium Enterprises Eco-Print in Bojonegoro - Winendra, RR Sekar Ayu Devi; Hoesny, Mariana Ulfah; Sakinah, Yanik Lailinas (Kirana Publisher (KNPub), 2024)
This study focuses on the development of a bilingual website for Cussaybienna, a Micro Small Medium Enterprise (MSMEs) specializing in eco-print products based in Bojonegoro. The primary goal is to enhance the company’s digital presence and expand its market reach by creating an online platform that caters to both local and international customers. The website provides detailed information about the company, including its profile, product catalog, contact details, and operational policies, all presented in both Indonesian and English. The research utilized the ADDIE model (Analysis, design, development, implementation, and evaluation) to guide the website’s development process systematically. Following its launch, the website was evaluated by 32 respondents, with result indicating a high level of satisfaction- 56.3% of respondents expressed being very satisfied with the overall website, while 59.4% strongly agreed that the content provided was highly informative. The findings suggest that the bilingual website effectively meets user expectations and significant contributes to the company’s digital marketing strategy, positioning Cussaybienna as a competitive cpmpetitor in the eco-fashion industry.